Vielstimmige Rede vom Unsagbaren: Dekonstruktion, Glaube und Kierkegaards pseudonyme Literatur - Schmidt, Jochen (Kierkegaard Studies. Monograph Series, 2008)
Main description: This study presents an interpretation of Kierkegaard’s writings 0Either / Or,0 0Repetition,0 and 0Fear and Trembling0 against the backdrop of postmodern philosophy of religion.